Patterns of Craniomaxillofacial Trauma at an Urban Level I Trauma Center - Olivia Jagiella-Lodise, BS; Christopher M. Stewart, MD; Hannah Moriarty, MD; Udayan Betarbet, MD; Angela Cheng, MD, FACS; Dina Amin, DDS, FACS (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. There is a paucity in the literature concerning craniomaxillofacial trauma (CMF) in the USA. Better recognition of these fracture patterns and their management clarifies how to best evaluate and treat them. Methods:. A retrospective chart review was conducted of CMF trauma patients who required surgical intervention at a level I trauma center between 2015 and 2018. Descriptive statistics and univariate and bivariate analyses were conducted (α = 0.05). Results:. A total of 1001 patients were included. Most patients were Black (n = 665; 66%) and/or male individuals (n = 813; 57%) with an average age of 37 years (range 15 -110). The most common etiologies were assault (n = 471; 44%), motor vehicle collision (n = 238; 22%), and fall (n = 117; 11%). The mechanism of injury was a determinant of fracture type (P = 0.045). The most common CMF injuries were mandibular fracture (n = 953; 95%), maxillary fracture (n = 815; 81%), and orbital fracture (n = 206; 21%). Male sex predicted panfacial fractures (P = 0.045). Black patients experienced more severe CMF trauma compared with other races (P < 0.001). ORIF was the most common treatment for mandibular (n = 481; 73%) and maxillary (n = 62; 66%) fractures. Conclusions:. Etiology and patterns of CMF trauma differ globally, with assault and motor vehicle collisions being the leading causative factors in our patient population. Patient demographics are relatively consistent worldwide, with most injuries occurring in 30- to 40-year-old men. This study offers insight into at-risk populations and guidance on their management.